1967
DOI: 10.1530/jrf.0.0130223
|View full text |Cite
|
Sign up to set email alerts
|

In-Vitro Uptake of Zinc by Boar Spermatozoa

Abstract: Summary. Boar spermatozoa accumulated zinc when stored in vitro in contact with boar seminal plasma. Zinc uptake was much more rapid when the spermatozoa were stored at 5\ s=deg\C than when stored at 30\s=deg\C.Freezing or the addition of the membrane-damaging agents, filipin or digitonin, before storage at 30\ s=deg\ C, caused rapid zinc uptake, but addition of the metabolic inhibitors, fluoride or iodoacetate did not accelerate zinc uptake. It is concluded that when membrane damage occurs spermatozoa accumul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

1972
1972
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 7 publications
2
6
0
Order By: Relevance
“…This may be partly due to the absorption of zinc by the spermatozoa suggested by the work of Westmoreland et al (1967) and confirmed by results of our own to be reported shortly.…”
Section: Other Secretionssupporting
confidence: 86%
See 1 more Smart Citation
“…This may be partly due to the absorption of zinc by the spermatozoa suggested by the work of Westmoreland et al (1967) and confirmed by results of our own to be reported shortly.…”
Section: Other Secretionssupporting
confidence: 86%
“…Apart from the values for whole semen reported by Westmoreland, First & Hoekstra (1967), there is no information in the literature on the zinc content of the seminal fluids of the boar. As part of an investigation of the occurrence and functions of zinc in the reproductive system of this animal, we have determined the zinc content of forty-six samples of seminal plasma and seventeen samples of vesicular secretion.…”
Section: Introductionmentioning
confidence: 97%
“…With respect to Zn, it has been shown in human that low seminal plasma Zn is associated with low motility, low sperm vitality, and infertility [Chia et al 2000]. In boars it has been shown that, when sperm cells are damaged, Zn accumulates in the sperm cells with a consequent reduction of Zn in SP [Westmoreland et al 1967].…”
Section: Discussionmentioning
confidence: 99%
“…Removal of zinc from the spermatozoa results in increased oxygen consumption after addition of succinate (Eliasson, Johnsen & Lindholmer, 1971;Huacuja et al, 1973) and increased formation of lipid peroxides (Johnsen & Eliasson, 1978a). The uptake or release of zinc by spermatozoa varies with species (Birnbaum, Hall & Lee, 1961;Lindholmer & Eliasson, 1974 (Westmoreland, First & Hoekstra, 1967).…”
Section: Introductionmentioning
confidence: 99%